Pengaruh Self Leadership Terhadap Kinerja Karyawan PT. PERKEBUNAN NUSANTARA V RIAU - Marnis '; Marzolina ' (Jurnal Ekonomi, 2010)
The purpose of this study is to examine the effect of Self leadership employee's on performance. Selfleadership is expected and positive relationship to employee's performance.Self leadership are defined as a process in which the leaders take actions to try to increase theirassociates’ awareness of what is right and important, to raise their associates..The population of this study is the employee of PTPN V in Riau, who has a position at middle manager.Using a sample of 146 middle manager, the author tested structural equation modeling (SEM). Selfleadership has a significant and positive effect on employee’s performance of PT PerkebunanNusantara V Riau.The result of this study has an important meaning to PT Perkebunan Nusantara V Riau and also toThe Plantation of The State Owned Enterprise. This study results a finding that the self leadership ofthe middle manager will increase the employee's performance .